2004
DOI: 10.2115/fiber.60.198
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Luminescent and Hole Transporting Rod-Coil Polymers

Abstract: Luminescent cyano-substituted distyrylbenzene derivatives were synthesized via Knoevenagel condensation reactions. By using these compounds as initiators, a series of rod-coil polymers were synthesized by the atom transfer radical polymerization of methacrylate containing hole transporting carbazole moiety in high yields except the initiator with dicyanovinyl end groups. Molecular weight up to 37000 and polydispersity indices not exceeding 1.6 were obtained. Photoluminescent spectra revealed the aggregation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Highly ordered microporous polymer films with honeycomb structure have been fabricated by a simple nontemplate method utilizing various types of block copolymers [1]- [8]. Although rod-coil type poly(p-phenylene)b-polystyreneor star-shaped polystyrene has been used in a pioneer study [1], other types of block copolymers have been also utilized including T-shape copolymer [5] and amphiphilic block copolymers [7] [8]. It is recognized that the mechanism for the formation of honeycomb structure can be explained by dissipative processes, where controlled condensation and growth of water droplets on the cold surfaces resulting from solvent evaporation of polymer solutions may be used to create a patterned surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly ordered microporous polymer films with honeycomb structure have been fabricated by a simple nontemplate method utilizing various types of block copolymers [1]- [8]. Although rod-coil type poly(p-phenylene)b-polystyreneor star-shaped polystyrene has been used in a pioneer study [1], other types of block copolymers have been also utilized including T-shape copolymer [5] and amphiphilic block copolymers [7] [8]. It is recognized that the mechanism for the formation of honeycomb structure can be explained by dissipative processes, where controlled condensation and growth of water droplets on the cold surfaces resulting from solvent evaporation of polymer solutions may be used to create a patterned surface.…”
Section: Introductionmentioning
confidence: 99%
“…Hayakawa et al reported that using a specially designed block copolymer, resulting porous films had highly ordered hierarchical structures over multiple length scales from angstroms to micrometers [6]. Furthermore, the surface aggregation of selective component is expected [5].…”
Section: Introductionmentioning
confidence: 99%